STUDY OF ENVIRONMENTALLY SOUND AND ENERGY-EFFICIENT METHODS OF CHEMICAL PRODUCTION IN THE CONTEXT OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT (American Journal of Business Management, Economics and Banking, 2026)
The article discusses modern approaches to the development of environmentally friendly and energy-efficient methods of chemical production. The key principles of sustainable development, the use of green technologies, new generation catalysts, renewable energy sources and closed production cycles are analyzed. efficiency.